Synthesis and Characterization of Co(II), Cu(II), Ni(II), Mn(II) and Pb(II) Complexes with 1,3-bis[(4-amino-5-mercapto)-1,2,4-triazol-3-yl]benzene - Maskar, P.T.; Chande, M.S.; Shaikh, M.M. (Asian Journal of Chemistry, 2010)
A series of complexes of Co(II), Cu(II), Ni(II), Mn(II) and Pb(II) with a polydentate ligand,1,3-bis[(4-amino-5-mercapto)-1,2,4-triazol- 3-yl] benzene, [H2-(BAMTB)] were synthesized and characterized on the basis of elemental analysis, molar conductance, diffused reflectance, magnetic susceptibility, spectral, thermal and X-ray studies. The antimicrobial and antifungal activity have also been checked. All the complexes are of 1:1 (M:L) stoichiometry. The IR spectra show that the tetradentate ligand coordinating through the SN-NS donor system. Various ESR parameters for the copper complex have been calculated. The complexes are monomeric in nature and non electrolytic in nature. Magnetic moment value indicates diamagnetic nature of Pb(II) complex and paramagnetic nature of Co(II), Cu(II), Ni(II) and Mn(II) complexes. The reflectance spectral data suggest a tetrahedral geometry for Pb(II) complex, an octahedral geometry for Co(II), Ni(II) and Mn(II) complex and a pseudotetrahedral geometry for Cu(II) complex. The complexes show high antimicrobial activities as compared with corresponding ligand but complexes do not show any antifungal activity. Diffractogram of present complexes do not show sharp refluxes indicate that they are amorphous in nature.